Information-Based Relative Consumption Effects - Samuelson, Larry (Econometrica, 2004)
Preferences exhibit relative consumption effects if a person's satisfaction with their own consumption appears to depend upon how much others are consuming. This paper examines a model of an evolutionary environment in which Nature optimally builds relative consumption effects into preferences in order to compensate for incomplete environmental information. Copyright Econometric Society 2004.